Membrane targeting and secretion of mutant uromodulin in familial juvenile hyperuricemic nephropathy. - Jennings, P; Aydin, S; Kotanko, P; Lechner, J; Lhotta, K; Williams, S; Thakker, R; Pfaller, W (2007)
Familial juvenile hyperuricemic nephropathy (FJHN) is an autosomal dominant genetic disorder that is characterized by hyperuricemia, gout, and tubulointerstitial nephritis. FJHN is caused by mutations in the UMOD gene, which encodes for uromodulin, the most abundant urinary protein. Herein is demonstrated that patients with FJHN and renal insufficiency exhibit a profound reduction in urinary uromodulin together with either elevated or decreased plasma uromodulin. One young patient with FJHN, however, had normal serum creatinine and normal urinary uromodulin with elevated plasma uromodulin. These observations suggest that there are different urinary and plasma uromodulin profiles in early and late disease and that there may be an altered direction of uromodulin secretion in the course of FJHN as a result of improper intracellular sorting of the mutated protein in the thick ascending limb. With the use of immunohistochemistry and a quantitative immunoassay, targeting and secretion of wild-type and mutant (C77Y and N128S) uromodulin were investigated in the polarized renal epithelial cell line LLC-PK1. In transfected cells, uromodulin mutants were targeted properly to the apical membrane but were secreted less efficiently to the apical compartment than wild-type protein. The expression of mutant uromodulin had no effect on caspase 3 activity. These results indicate that the mutations studied do not impair glycosyl-phosphatidylinositol-mediated apical targeting of the protein but do affect apical secretion. Because the mutant proteins are secreted as efficiently as wild type to the basolateral compartment, the possibility arises that interactions with the immune system at the site of secretion are a contributing factor to the development of tubulointerstitial nephritis in FJHN.